Teach Yourself : French - Wilson, Norman Scarlyn (London The English Universities Press Ltd., 1967)
The purpose of this book is not to teach you when and where to use and to not use a comma or a semi-colon, or how to say hello, goodbye, and "Where is the gate to my plane?" The purpose is stated in the subtitle: to quickly and easily learn the French language. It should be obvious to a beginner that the book is not suited to any other purpose. If one wants to learn the finer points of grammar and punctuation, then he should purchase a concise or comprehensive grammar which deals with such issues. If one wants to know how to say certain phrases while on a trip, then he should purchase a traveler's phrase book. A beginner should not be concerned with punctuation and greetings if he is at home teaching himself. Besides, he will learn the basic, proper punctuation simply through the very reading itself. Is the beginner going to be writing a resume to apply for a French-speaking job in France or Quebec, or even in the Congo?
Include Vocabulary and Note.
Keywords: French Language